Differences of Student's Motivation and Biology Learning Outcomes Through Jigsaw II Learning Model and NHT Learning Model - Winanti, Zuan Puri; Amalia, Mei Widya (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2022)
The aims of this study are: (1) to find out whether there are differences in the motivation to learn Biology of students who are taught through Jigsaw II and NHT learning models and to find out whether there are differences in learning outcomes of Biology students who are taught through Jigsaw II and NHT learning models at senior high school of SMA Negeri 1 Tumpang, Indonesia. This study used a quasi-experimental method with a comparative design. The sample in this study were students of class X-2 who were taught using the Jigsaw II learning model and class X-3 students who were taught using the NHT learning model. Analysis of the data used to determine differences in student motivation, namely Anova and to determine differences in student cognitive, affective, and psychomotor learning outcomes, namely Anacova. Based on the results of data analysis, it was found that there was no difference between the biology learning motivation of students who were taught through Jisgsaw II and NHT learning models. In addition, it was found that there was no difference between cognitive learning outcomes, affective learning outcomes, and psychomotor learning outcomes for Biology students who were taught through Jigsaw II and NHT learning models. Thus, it can be concluded that Jigsaw II learning model and NHT learning model have no variation and have good similarities for students' self-development potential.